2016
DOI: 10.1177/1938640016679697
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes of Particulated Juvenile Articular Cartilage and Bone Marrow Aspirate Concentrate for Articular Cartilage Lesions of the Talus

Abstract: Therapeutic, Level IV: Retrospective, Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
(60 reference statements)
1
33
0
Order By: Relevance
“…The overall clinical outcomes in our study parallel the current limited data on PJCAT for treatment of OCLTs. 8,10,23,36,37 However, some authors have reported on PJCAT with concomitant procedures such as realignment osteotomies and ligamentous stabilizations. 8,36,37 In the current study, overall patient-reported ankle pain improved significantly by 51%, compared to preoperative levels following PJCAT for treatment of symptomatic OCLTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall clinical outcomes in our study parallel the current limited data on PJCAT for treatment of OCLTs. 8,10,23,36,37 However, some authors have reported on PJCAT with concomitant procedures such as realignment osteotomies and ligamentous stabilizations. 8,36,37 In the current study, overall patient-reported ankle pain improved significantly by 51%, compared to preoperative levels following PJCAT for treatment of symptomatic OCLTs.…”
Section: Discussionmentioning
confidence: 99%
“…With PJCAT for treatment of OCLTs in its nascent adoption, there is a paucity of literature regarding intermediate or even short-term outcomes following its use. 4,8,10,23,36,37 Three retrospective series have demonstrated encouraging short-term clinical and functional outcomes following arthroscopic and open PJCAT. 8,10,36 Two of these series were confounded by concomitant procedures other than isolated PJCAT.…”
mentioning
confidence: 99%
“…These were conducted in either the knee [71, 72] or the ankle joint [73, 74] (Table 2). Microfracture was the main marrow stimulation technique, applied in three studies [7173], subchondral drilling only once [74]. In all the investigations, BMA was harvested from the iliac crest and processed with various commercially available centrifuge systems to generate BMAC.…”
Section: Effects Of Bone Marrow Aspirate-enhanced Marrow Stimulatimentioning
confidence: 99%
“…MRI also revealed that BMAC-enhanced microfracture induced significantly less fissuring and fibrillation of the articular cartilage surface than microfracture treatment without adjunct. Lanham et al evaluated 12 patients with full-thickness chondral defects of the talus (6-7 mm in depth) treated either with BMAC-enhanced subchondral drilling covered by a collagen scaffold or with particulated juvenile articular cartilage [74]. The collagen scaffold consisted of a hydrated matrix of bovine collagen and glycosaminoglycans.…”
Section: Effects Of Bone Marrow Aspirate-enhanced Marrow Stimulatimentioning
confidence: 99%
“…Improvement was seen in pain and function. 1,8,12,14,16 The purpose of this article was to evaluate clinical and functional outcomes after the use of PJCAT and to identify patient and OLT attributes that influence outcomes following this technique. We hypothesized that PJCAT would be a safe and effective treatment for OLTs.…”
mentioning
confidence: 99%